Inter-Species and Inter-Organ Differences in Stable C and N Isotope Signatures of Macrophytes from the Largest Freshwater Lake in China - Zhang, Meng; Zhang, Jinmei; Yao, Na; Zhang, Peiyu; Liu, Zugen; Zhu, Guorong; Xu, Jun; Zhong, Ruixue; Xie, Ping (Journal of Environmental Science and Engineering Technology, 2023)
Macrophytes play important roles in shallow aquatic ecosystems. Stable isotope signatures of macrophytes indicate the environmental conditions and macrophyte contributions to food webs. However, macrophyte isotope signatures have been studied less than isotope signatures of other organisms. We determined the stable C and N isotope signatures of 10 aquatic plant species from Poyang Lake wetland (Wucheng, Yongxiu County) and Nanji wetland (Nanjishan, Xinjian County) in Jiangxi Province, which are Chinese national nature reserves, among different seasons. The isotope signatures for different species and seasons were significantly different. The dominant macrophyte species were Potamogeton malaianus and Nymphoides peltatum. The isotope signatures for different organs of these two species were determined. Both δ13C and δ15N values were higher for P. malaianus than for N. peltatum stems, roots and leaves, and δ13C varied less for N. peltatum than for P. malaianus organs. The δ13C and δ15N values for P. malaianus organs increased in the order roots<stems<leaves. δ13C values for N. peltatum organs decreased in the order roots>stems>leaves, and δ15N values for N. peltatum organs increased in the order roots<stems<leaves. The stable C and N isotope signatures for P. malaianus and N. peltatum may be controlled by various factors including macrophyte life history, external sources of C/N, and the amount of water in the wetland. These results provided a theoretical reference and experimental data support for detecting the flow trend of C & N elements and environment changes in the lake by the δ13C and δ15N values of euhydrophytes.